Rancang Bangun Aplikasi Penjadwalan Penyewaan Peralatan Event Organizer (Studi Kasus: PT. Geo Given Visi Mandiri) - Wijaya, Farid Ardi; Arifin, Mochammad; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: PT. Given Geo Vision Mandiri (PT. GGM) is a services company in the form of event organizer. Problems the business process is hampered by the ever-expanding areas of activity undertaken event. As a result, companies have difficulties in providing services such as the supply of goods that are not available in the warehouse and time of event which simultaneously. Handling of leasing are constrained by the available tools are not available in the warehouse and have to wait for confirmation from the company relationship, have an impact on the length of service of the response to the transaction ordering. The absence scheduling structured activities often lead to trouble handling the same event or activity near-term implementation time. Enterprise systems needed to support the process of marketing, sales, and the provision of services to customers. This system has the functionality that is providing services to consumers. The system can be computerized so that it can handle the registration process or customer registration schedule for processing event equipment rental services. The method used in the process of scheduling the method of SAW (Simple Additive weighting). SAW aims to design and make applications easier scheduling rental.